Synergistic Effects of Salinity and AMPEP Concentrations on the Growth, Pigment Accumulation, and Biochemical Composition of Chlorella sorokiniana Culture - Sarri, Jurmin H.; Amlani, Merilyn Q.; Jalilul, J-Nadine M.; Jeva, Marcelita A.; Kissae, Al-Nasrif H.; Jalaidi, Noriam L.; Ensano, Fatima Nhidzlah T. (HAYATI Journal of Biosciences, 2026)
Microalgae, particularly Chlorella sorokiniana, are widely recognized for their applications in aquaculture, biofuel production, and nutraceutical industries due to their high biomass yield and valuable biochemical composition. However, optimizing culture conditions remains essential for improving growth and metabolite production. This study investigated the combined effects of sodium chloride (NaCl) and Ascophyllum (Acadian) Marine Plant Extract Powder (AMPEP) concentrations in BG-11 medium on the growth, pigment accumulation, and total phenolic content of C. sorokiniana. Eight treatments were evaluated: T1 (control BG-11 only), T2 (AMPEP only), T3 (NaCl only), T4 (NaCl + AMPEP), T5 (NaCl + AMPEP + BG-11), T6 (15 g L-1 NaCl + 100 mg L-1 AMPEP + BG-11), T7 (20 g L-1 NaCl + 150 mg L-1 AMPEP + BG-11), and T8 (25 g L-1 NaCl + 200 mg L-1 AMPEP + BG-11). Results showed that T6 achieved the highest cell density, reaching 10.14-fold cell mL-1 compared with the control. The highest specific growth rate and dry weight were observed in T8 at 0.18±0.01 day-1 and 0.14±0.00 g L-1, respectively. Cell size was significantly larger (p<0.05) in T6, T7, and T8. For pigment accumulation, T5 recorded the highest chlorophyll a (25.54±1.42 μg mL-1), total carotenoids (97±0.88 μg mL-1), and while the same treatment also yielded the highest total phenolic content (8.72±0.87 mg GAE g-1 DW). These findings demonstrate that NaCl-AMPEP supplementation enhances biomass, pigment accumulation, and biochemical composition in C. sorokiniana.